THE USE OF ONLINE LEARNING MEDIA TO IMPROVE STUDENTS 'CREATIVE THINKING ABILITY DURING COVID 19 PANDEMIC - Agus Hidayatullah (Cakrawala Pedagogik, 2021)
The government's policy to stop the Covid-19 pandemic has a huge impact on the education system in Indonesia. The teaching and learning process should not be done in class directly as usual but must be carried out by a distance learning process or online learning. The massive development of science and technology emphasizes students especially to be able to improve their performances. One aspect here is the ability to think creatively. The online learning requires students to think creatively about how to run the learning process effectively. The effectiveness of online learning really considered so that students can comprehend the material as well as offline learning. The purpose of this research is to find out and understand how the effectiveness of online learning using the Zoom Meeting application. This study uses a qualitative method. The data collection technique was carried out by interviewing via Google Form and Whatsapp to third semester classes in the Islamic Education Department of STAI Syekh Manshur Pandeglang. By using online learning, it encourages students to be more active in their learning processes. Many features in Zoom Meeting make learning process more interesting. In addition, the learning materials conveyed by the lecturers can be grasped by the students.